Course of Preexisting Migraine Following Spontaneous Subarachnoid Hemorrhage - Valdueza, José Manuel; Dreier, Jens Peter; Woitzik, Johannes; Dohmen, Christian; Sakowitz, Oliver; Platz, Johannes; Leistner-Glaess, Stefanie; Witt, Victoria Dorothea (Frontiers in Neurology, 2022)
Background Our objective was to observe the course of preexisting migraine following subarachnoid hemorrhage (SAH) in patients with and without craniotomy. Methods We designed an exploratory analysis and hypothesis-generating study of prospectively collected data starting by recruiting patients suffering from SAH with the Hunt and Hess scale score of ≤ 4. Out of 994 cases, we identified 46 patients with preexisting active migraine defined by at least four attacks in the year before SAH. According to the treatment, we subdivided the patients into two groups: the first group included patients with surgical aneurysm clipping with transection of the middle meningeal artery (MMA) and accompanying trigeminal nerve branches and the second group included patients with endovascular aneurysm coiling or without any interventional treatment. During the follow-up, we recorded the course of migraine frequency, duration, intensity, and character. Results For both groups (craniotomy n = 31, without craniotomy n = 15), a significant improvement regarding the preexisting migraine during a mean follow-up of 46 months (min. 12 months, max. 114 months) was seen regarding complete remission or at least >50% reduction in migraine attacks (p < 0.001 and p = 0.01). On comparing the groups, this effect was significantly more pronounced in patients with craniotomy (for no recurrence of migraine: p = 0.049). After craniotomy, 77.4% of the patients had no further attacks of migraine headache and 19.4% showed a reduction of >50% while only 2.2% did not report any relevant change. In the non-surgical group, 46.7% had no further migraine attacks, 20% had a reduction of >50%, while no change was noted in 33.3%. Conclusions Our study provides evidence that the dura mater might be related to migraine headaches and that transection of the MMA and accompanying trigeminal dural nerve branches might disrupt the pathway leading to a reduction of migraine attacks. However, coiling alone ameliorated migraine complaints.